Multilocus phylogeny of Bornean Bent-Toed geckos (Gekkonidae:Cyrtodactylus) reveals hidden diversity, taxonomic disarray, and novelbiogeographic patterns - Davis, Hayden R.; Kin, Onn Chan; Das, Indraneil; Brennan, Ian G.; Karin, Benjamin R.; Jackman, Todd R.; Brown, Rafe M.; Iskandar, Djoko T.; Izneil, Nashriq; Grismeri, L. Lee; Bauer, Aaron M. (Elsevier, 2020)
The gekkonid genusCyrtodactylusis a highly diverse group of lizards (280 + species), which covers an expansivegeographic range. Although this genus has been the focus of many taxonomic and molecular systematic studies,species on the Southeast Asian island of Borneo have remained understudied, leading to an unclear evolutionaryhistory with cascading effects on taxonomy and biogeographic inferences. We assembled the most compre-hensive multilocus Bornean dataset (one mitochondrial and three nuclear loci) that included 129 novel se-quences and representatives from each knownCyrtodactylusspecies on the island to validate taxonomic status,assess species diversity, and elucidate biogeographic patterns. Our results uncovered a high proportion of crypticdiversity and revealed numerous taxonomic complications, especially within theC. consobrinus, C. malayanus,andC. pubisulcusgroups. Comparisons of pairwise genetic distances and a preliminary species delimitationanalysis using the Automatic Barcode Gap Discovery (ABGD) method demonstrated that some wide-rangingspecies on Borneo likely comprise multiple distinct and deeply divergent lineages, each with more restricteddistributional ranges. We also tested the prevailing biogeographic hypothesis of a single invasion from Borneointo the Philippines. Our analyses revealed that Philippine taxa were not monophyletic, but were likely derivedfrom multiple separate invasions into the geopolitical areas comprising the Philippines. Although our in-vestigation of BorneanCyrtodactylusis the most comprehensive to-date, it highlights the need for expandedtaxonomic sampling and suggests that our knowledge of the evolutionary history, systematics, and biogeographyof BorneanCyrtodactylusis far from complete.